Characterization and lymphocyte proliferation activity of an oligosaccharide degraded from Astragalus polysaccharide. Issue 7 (28th June 2017) - Zhu, Zhen-Yuan; Zhang, Jin-Yu; Liu, Fei; Chen, Ling; Chen, Li-Jing; Tang, Yun
Abstract : An Astragalus oligosaccharide (AOS) degraded from Astragalus polysaccharide (APS) and purified by membrane dialysis and silicon gel chromatography is studied in this paper. Abstract : An Astragalus oligosaccharide (AOS) degraded from Astragalus polysaccharide (APS) and purified by membrane dialysis and silicon gel chromatography is studied in this paper. The structural features of AOS were investigated by a combination of chemical and instrumental analysis, such as monosaccharide analysis, periodate oxidation-Smith degradation, methylation analysis, electrospray ionization mass spectrometry (ESI-MS), Fourier transform infrared (FT-IR) spectrometry and nuclear magnetic resonance (NMR). The results indicated that AOS is an octasaccharide that consists of (3→)-linked-Rha, (1→3)-linked-Rha, (1→3, 4)-linked-Araf, (1→3)-linked-Gal, terminal-linked-Gal and terminal-linked-Glc. The effects of AOS on cyclophosphamide-induced immunosuppression were determined by various studies, such as the proliferation of nucleated marrow, red blood cell (RBC) and white blood cell (WBC) populations, growth of the spleen and thymus, and increases in hemoglobin (HGB) concentration and granulocyte-macrophage colony stimulating factor (GM-CSF) level. The results indicated that AOS can restore cyclophosphamide-induced immunosuppression by stimulating the secretion of GM-CSF, which promoted the differentiation of progenitor cells after proliferation.